Benefits, perceived and actual risks and barriers to egg consumption in low- and middle-income countries - Tiwari, Chhavi; Balehegn, Mulubrhan; Adesogan, Adegbola T.; McKune, Sarah L. (Frontiers in Animal Science, 2023)
Eggs like other animal-source foods (ASFs), contain an array of macro and micronutrients that promote physical and cognitive growth, nutrition, and health outcomes. Hence, they can be used to reduce rampant undernutrition in low-and middle-income countries (LMICs). Yet consumption of eggs remains low in such countries for various reasons. Given their potential as a tool for reducing malnutrition, this paper reviews the literature on the benefits, risks, and barriers to egg consumption in LMICs. Research indicates that egg consumption is associated with several nutritional and health benefits in newborns, young children, and pregnant and lactating women, but few studies on other groups exist. Effects of egg consumption on diet-related chronic diseases seem to be inconclusive, and early introduction of eggs to infants has reduced allergy risk of eggs later in life in several studies. Some main barriers to egg consumption in LMIC include unaffordability and unavailability, partly due to low poultry productivity, high poultry feed prices, cultural beliefs, and social taboos, many of which disproportionately restrict egg consumption among children and pregnant women. The evidence supports egg intake as a mechanism for meeting nutrient recommendations and a healthy diet in LMIC.